Link Budget Simulation and Analysis for Cambium Radio in Telkomsat Radio IP Service - Marchellius Fernando Warnadi; Muhammad Syaiful Aliim; Norma Amalia (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2024)
The Final Project examines link budget calculations for Cambium brand radio devices using Link Planner to support Telkomsat’s transition from partner-managed to self-managed Radio IP services. A successful transition requires proper planning, including identifying equivalent radio devices and conducting link budget analysis. The process involves determining transmission distance, antenna height, and selecting suitable devices. Key parameters in the link budget calculation include Freznel Zone Clearance (FZC), Free Space Loss (FSL), Effective Isotropic Radiated Power (EIRP), Received Signal Level (RSL), System Operating Margin (SOM), Availibility (%), and Bandwidth (Mbps). Among 31 customers, 100% met standart EIRP values, 87% had good RSL, and 13% were very good. Additionally, 94% met SOM standards, while 6% fell into the poor category. Based on these result, it can be concluded that this research was successful, as the obtained result align with the established standards.